PERAN RTH ALUN-ALUN RATU ZALECHA TERHADAP KENYAMANAN LINGKUNGAN BERDASARKAN PERSEPSI MASYARAKAT DAN INDEKS KETIDAKNYAMANAN (Studi Kasus RTH Alun-Alun Ratu Zalecha, Martapura Kalimantan Selatan) - Muhammad Wahyu; Danang Biyatmoko; Hilda Susanti; Fatmawati Fatmawati (EnviroScienteae, 2023)
Based on statistical data (Banjar District in Figures, 2016), it was found that there was an increase in population density from 2013 to 115 people / km2, by 2014 117 people / km2 and 2015 by 119 souls / km2. To support human needs and activities, it takes a lot of space, especially built space. The purpose of this study is to analyze the public perception about the role of green space on environmental comfort in RTH Ratu Zalecha Square and analyze the role of RTH Queen Square Zalecha to the comfort of environment based on the index of discomfort. The research method used is survey method and quantitative descriptive analysis. The survey method aims to observe the condition of research sites such as physical condition and RTH characteristics. The survey also aims to determine the point of data collection, identify the green space structure, and take the microclimate primary data. The result of this research shows that the level of public perception on the comfort of RTH Alun-Alun Ratu Zalecha has positive effect for 84 respondent (87,5%) and 12 respondents (12,5%).  This indicates that H0 is accepted which presumes that there is positive effect of RTH of Queen of Zalecha against the comfort of environment and H1 is rejected and Chi-Square calculation shows that X2H value is 96,47 bigger than X2 table 5% that is 5,991 so that H0 is accepted, meaning there is a significant difference between the three levels of public perception towards the comfort of the environment with the highest level of positive perception is in the category of a very influential role and affect the comfort of the environment. Based on observation data at the study location, the average daily discomfort index at location I (on the surface), location I (1.4 meters), location II (1.4 meters), location III (1.4) meters) between 80,2-81,7 which is in the interval of the value of DI> 80, which means that 100% of respondents stated that all research locations in the category were uncomfortable for humans.